1) y=2√x = 2x^(¹/₂ -3) = 2x^(-2.5)
x³
y' = 2*(-2.5)x^(-2.5-1) = -5x^(-3.5) = _ 5
(x³) √x
2) y= 6∛x = 6x^(¹/₃ - ¹/₂) = 6x^(⁻¹/₆)
√x
y' = 6*(-¹/₆) x^(-¹/₆ -1)= -x^(-⁷/₆) = - 1
x (⁶√x)
3) y=⁴√(1/x³) = 1 = x^(-³/₄)
x^(³/₄)
y' = -³/₄ x^(-³/₄ - ⁴/₄) = -³/₄ x^(⁻⁷/₄) = - 3
4x (⁴√(x³))
4) y=∛(1/x⁻²) = 1 = x^(²/₃)
x^(⁻²/₃)
y' =²/₃ x^(²/₃ - ³/₃) = ²/₃ x^(-¹/₃) = 2
3 ∛x
5) f(x) =x⁻² √x ∛x = x^(-2 + ¹/₂ + ¹/₃) = x^(-¹²/₆ + ³/₆ + ²/₆) = x^(⁻⁷/₆)
f(x)' = -⁷/₆ x^(-⁷/₆ - ⁶/₆) = -⁷/₆ x^(⁻¹³/₆) = -7
6x² (⁶√x)
6) S= ∛t ∛(t²) = t^(¹/₃ + ²/₃ - 1) =t⁰ = 1
t√1
S' = (1)' = 0